PEMBELAJARAN TARI JAIPONGAN UNTUK ANAK USIA DINI DI SANGGAR MAYANG BINANGKIT - Rahmawati, Devi (Jurnal Seni dan Pembelajaran, 2023)
AbstractJaipong dance is a West Javanest dance art created by an artist from Bandung named Gugum Gumbira Tirasonjaya. Jaipongan is also the name for the works of Gugum Gumbira from 1967 until now including the names Oray Welang, Keser Bojong, Pancung Bojong and many more (Kurniati, 1995). The Mayang Binangkit studio is located in Indihiang, the city of Tasikmalaya which deals whit the fields of cultural arts focusing on dance. There are 10 children who take part in the studio, with an average age of 4 to 9 years. They like dance because of their high interest, some are obsessed with their friends who have attended before, and they feel comfortable when practicing with jaipongan material. Learning at an early age of the jaipong dance became one of the foundations for me to take up this dance because I was the loss of the basic dance movements, where the basic froms of movements with the creation dance. The benefits of me taking jaipong dance at the Mayang Binangkit studio are that young children are able to make flexible movements precisely and have a clear structure so that they are able to distinguish between traditional and creative movements.Keyword:dance learning, jaipong dance, early age